Kritik Amartya Sen atas Teori Keadilan John Rawls: Kritik Pendekatan Komparatif atas Pendekatan Institusionalisme - Sunaryo Hasan (Respons: Jurnal Etika Sosial, 2018)
ABSTRACT: This article shows Amartya Sen’s criticism to John Rawls’ theory of justice. The main criticism is Rawls’ institutionalism approach in his theory of justice. This approach, Sen traces, is based on contractarian paradigm. By this paradigm, perspective of justice is limitted in citizenship contract. A person deserves justice as far as he is citizen. In this perspective, collective decision is only based on those which are citizen. Sen called this paradigm closed impartiality, not open impartiality. Whereas his idea of justice is much broader and beyond the limit of citizenship. If we think about justice, it is not only just for those who are bound in citizenship contract, but also for those who are not. His other criticism is about asumption in theory of justice, which is perfect justice. Sen say that comparative justice does not try to make a perfect justice in this world. What the term is trying is to make life of people less unjust than before. KEYWORDS: Institusionalisme, komparatif, hal-hal pokok, perilaku aktual, niti, nyaya, less unjust